Validation of instrument in measuring English language reading anxiety among undergraduates in two private universities - Kalthom Husain; Puziah Abd Wahab; Aishah Amirah Zainal Abidin; Haniza Othman; Mohd Salihin Hafizi Mohd Fauzi; Aida Nasirah Abdullah (Penerbit Universiti Kebangsaan Malaysia, 2020)
Anxiety is associated as a state of uneasiness and apprehension about uncertainties. This paper describes the validation process of an instrument to measure reading anxiety among the English as a Foreign Language Learners (EFL). This instrument is adopted and adapted from English Language Foreign Language Anxiety Instrument (ELFRAI) developed by Masoud Zoghi (2012). However, some of the items in ELFRAI were reconstructed to reduce ambiguity. It is a nonverbal self-reported instrument measures to measure English Language reading anxiety. The instrument is structured into two parts namely demography and causes of reading anxiety and contains 8 items and 27 items respectively. To identify reading anxiety among EFL learners, a total of 366 responses at two states private universities colleges located in Malaysia were analysed. This study adopts the quantitative approach as its research methodology. It uses SPSS version 22 to analyse the findings gathered. The results of the study depicts a reliability Cronbach’s Alpha 0.927, hence it supports the validity of the instrument